EKSISTENSI KEBERADAAN SANKSI UU TPKS MEMBERIKAN PERLINDUNGAN BAGI KORBAN PELECEHAN SEKSUAL DIINDONESIA - Fajar Yaskur; Ifahda Pratama Hapsari (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
This study aims to determine the existence of the sanctions of the sexual violence crime act called (TPKS) in various ways to provide preventive and repressive legal protection for victims of sexual violence. They are compiled using the normative method, which includes the study of laws and regulations, legal theories, opinions of experts, and other legal materials. Sexual harassment is an act that has a severe impact on victims, and the existence of the TPKS Law Number 12 of 2022 in Indonesia was formed as a legal umbrella effort and as an effort to renew punitive sanctions to follow up firmly on perpetrators of sexual harassment. The Criminal Code that has been amended and regulated in the Criminal Code Number 1 of 2023, which is explained in Chapter XV concerning criminal acts of decency, mainly regulated in articles 414 to 423 of the Criminal Code, has also not been able to provide complete legal protection for victims of sexual harassment. The Criminal Code also does not mention explicitly or explicitly the problem of sexual abuse. The result of this research is to provide explanation and legal protection for victims who are mentally disturbed due to the impact of sexual harassment and can provide punishment for perpetrators regardless of their status to create a deterrent effect for the perpetrators.